Delayed stomach necrosis in a patient with injured celiac artery branches after penetrating abdominal trauma - Yoshito Ishiki; Toru Takiguchi; Shiei Kim; Masatoku Arai; Hiromoto Ishii; Jun Hagiwara; Osahiko Hagiwara; Tomoko Ogasawara; Shintaro Teraoka; Futoshi Ogawa; Shoji Yokobori (Trauma Case Reports, 2023)
Injuries of the celiac artery and its branches are rare, but potentially lethal. Ligation of these arteries is performed to control significant hemorrhage. However, few reports have described the adverse effects of ligating these arteries.A 69-year-old woman with a self-inflicted stab wound was brought to our hospital. Her blood pressure could not be measured, therefore aortic cross-clamping was performed, and epinephrine was administered for resuscitation, an emergency laparotomy was performed, and the roots of splenic artery and common hepatic artery were ligated. The left gastric artery which was anomalous and arose directly from the aorta, was also injured and had to be ligated. Norepinephrine was required after the surgery. Enhanced computed tomography performed on hospital day 4 revealed a disrupted celiac artery. The patient developed gastric necrosis on hospital day 23 and, hence, underwent total gastrectomy was performed.The possibility of delayed stomach necrosis should be considered during the postoperative management of patients who undergo ligation of all of the celiac artery branches and experience global hypoperfusion after the surgery.